THE PRESENCE OF GLOBAL VALUE CHAIN IN COASTAL MARINE TOURISM - Goni, Joklan I. C; Yustika, Besty Puspa (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2019)
This paper identifies the actors in the Global Value Chain (GVC) for coastal and marine tourism (CMT) in the Thousand Islands and analyses SWOT for the lodging and transportation sectors. In-depth interviews and focus group discussions were conducted with the actors who are managers of lodgings and travel agents, transportation business owners, tour guides, and government organizations. This study first reveals the stakeholders involved in the GVC are the community, government, and private companies. It also confirms the tourist type that is dominated by organized mass tourists. Secondly, SWOT analysis was used to describe the situation of the lodging and transportation sectors. Infrastructure is the main concern of transportation, while for accommodations, there are wide ranges of resorts and homestays with the majority managed by the local community. In addition, technology improvement also contributes to the ease of information access, facilities, and tourism product purchase. Keywords: Global Value Chain Model, Coastal Marine Tourism, Thousand Islands, SWOT Analysis